Rapid and sensitive XAFS using a tunable X-ray undulator at BL10XU of SPring-8 - Oyanagi, H (Journal of synchrotron radiation, 2000)
The design and performance of the high-brilliance XAFS facility at BL10XU of SPring-8, aimed at rapid and sensitive measurement of X-ray absorption fine structure (XAFS), is reported. Both undulator gap and double-crystal monochromator have been successfully controlled covering a wide energy range (5-30 keV). A versatile goniometer system, consisting of two independent high-precision goniometers, is capable of polarized XAFS in fluorescence mode and surface-sensitive experiments using a grazing-incidence geometry. By sharing major components, i.e. a monolithic Ge 100-pixel array detector and a closed-cycle He cryostat, both polarized XAFS and X-ray standing wave (XSW) experiments can be performed at low temperature (15-300 K). The performance of the spectrometer has been evaluated by recording XAFS spectra in transmission mode